Electrochemical reactors equipped with BDD electrodes: Geometrical aspects and applications in water treatment. Issue 4 (August 2021) - Cornejo, Oscar M.; Murrieta, María F.; Castañeda, Locksley F.; Nava, José L.
Highlights: Configurations of electrochemical reactors with 2D and 3D BDD electrodes. Wastewater treatment: persistent organic pollutants (POPs) destruction, disinfection. Preconditioning of cooling water, electrosynthesis of chemicals by CO2 reduction. Filter-press cells with BDD plates enable control flow velocity and current density. Pilot plant + filter-press cell allowed 100% POPs oxidation with 5.92 kWh m −3 . Abstract: The importance of geometrical aspects of different electrochemical reactors (ECRs), equipped with BDD electrodes, on water treatment performance is analyzed. The treatments are disinfection of water, incineration of persistent organic pollutants (POPs) in effluents, cooling water preconditioning, and electrosynthesis of chemicals from water containing CO2 . The incineration of POPs has been carried out by different electrochemical advanced oxidation processes (EAOPs) like anodic oxidation (AO), persulfate activation by electrogenerated H2 O2 and AO, and electro-Fenton (EF). This communication analyzes continuous ECRs' success, homemade or commercial, in a single pass and recirculation mode of operation, ranging from fundamental studies to pilot plants.